PERFORMANCE-BASED ASSESSMENT AS A CURRENT TREND IN ELT: INVESTIGATING ITS WASHBACK EFFECTS ON SECONDARY-SCHOOL STUDENTS LEARNING - Sumardi, Sumardi (Kajian Linguistik dan Sastra, 2017)
Assessment is an integral part of an English teachersâ instruction since it enables them to visualize the extent of successful instructions. However, teachers might not pay much attention to their role to help their students improve their learning. Even, many English language teachers seem to focus more on traditional formats of assessment such as multiple choice, true false, matching type, etc. and pay little attention to the washback effects of these kinds of assessment on studentsâ learning. This paper argues that a traditional assessment has at least two fundamental flaws. There is a little chance to identify the studentsâ factual skills as it only focuses on formal assessment. In addition, it only focuses on achievement of high scores under test conditions. This orientation can be misleading to the nature of language instruction itself. Therefore, this research article explores the washback effects of performance-based assessment as a current trend in English Language Teaching (ELT) in secondary-school studentsâ learning. To investigate this issue, in-depth interview, classroom observation, and document analysis were employed as the data collection methods. The merits of the research are to indicate how to arrange performance-based assessment and to identify its washback effects in the studentsâ learning. The results conclude that performance-based assessment encouraged and motivated students to learn more. Studentsâ perception in this type of assessment was positive and they strived to be more successful in their learning.Â Keywords: performance-based assessment, washback effects, student learning.